Six-Minutes Walk Test Characteristics in Geriatric Outpatient Clinic at Dr. Hasan Sadikin General Hospital Bandung - Hanifah Hanifah; Yuni Susanti Pratiwi; Tri Damiati Panjdi (Althea Medical Journal, 2019)
Background: The six-minute walk test (6MWT) is a safe, easy to perform, and inexpensive test to evaluate the functional and exercise capacity in the elderly. The purpose of this study was to describe the 6MWT distance achieved among elderly patients.Methods: This descriptive study was conducted from January to November 2014 using medical records in the geriatric outpatient clinic of the Department of Internal Medicine at Dr. Hasan Sadikin General Hospital from 2012 to 2014. The main variable was the distance achieved by the 6MWT, compared based on age, sex, and body mass index.Results: The average distance of the 6MWT in 122 elderly was 237.56 m. The highest results were in the youngest age group of 60–69 year old with an average distance of 243.87 m. A male elderly patients had an average distance of 245.26 m, and the elderly with high body mass index had 248.57 m.Conclusions: The distance achieved among the elderly during the 6MWT is relatively short. Increased physical activity such as walking is recommended for the elderly.